A Periodic Joint Replenishment Inventory Model with Quantity Discounts for Full Truckload Ordering. - Dawani, Khalil (2015)
Multi-item inventory environment is considered to be a challenging environment for wholesalers to manage and control. Suppliers offer quantity discount schedules on full truckloads to wholesalers, in order to encourage wholesalers to replenish products in large quantities to benefit from economies of scale in production, and utilise the transportation methods. In this dissertation, a mixed integer linear programming model will be developed to group products into full truckload replenishment groups to benefit from quantity discount schedules, while aiming to minimise the total cost of replenishment. The model will be tested using different demand scenarios aiming to exploit different possible outcomes of the model. The testing procedure will be performed using different setup cost schemes, and results will be compared. The cost and order frequency aspects of the replenishment policies will be the main criteria of comparison between the different setup cost schemes. The results obtained from the grouping procedure from grouping model showed excellent performance of the model, and were consistent with the cost analysis carried out in order to explain the model's behaviour. This grouping model can be considered as an initial step towards a direct grouping model technique.